DAYA SAING PRODUK TURUNAN SUSU INDONESIA DI PASAR DUNIA - Lina Yanti; Widyastutik Widyastutik (School of Business, Bogor Agricultural University (SB-IPB), 2012)
ABSTRACTThis research purposes were (1) to measures the competitiveness of Indonesian milk derivative product in international market based on its comparative advantage, (2) to analyze the dynamics of Indonesian milk and also to analyze the commodity’s competitive position in the international market through its dynamic export product performance, (3) to analyze dominant factors that influencing Indonesian dairy export growth based on constant market share analysis. The analysis methods used to measure the competitiveness of Indonesian milk in this research are based on revealed comparative advantage analysis, Export product dynamic analysis (EPD), and constant market share analysis. The result from RCA showed that the Indonesian milk derivative products which are Milk not concentrated nor sweetened 1–6% fat (HS 040120), Milk and cream, concentrated or sweetened (HS 0402) and Buttermilk, curdled milk, cream, kephir, etc (HS 040390) do not have comparative advantage but for Milk and cream powder unsweetened > 1,5% fat (HS 040221), Milk and cream nes sweetened or concentrated (HS 040299) and Cereal, flour, starch, milk preparations and products (HS19) have comparative advantage. The EPD found that all Indonesian milk derivative products are included in the Rising Star position. The result test using CMS analysis concluded that the most significant factor which affect the export growth for Indonesian HS 040390 and HS 0402 derivative products are the import growth effect, HS 19 is mainly dominated by commodity composition effect, and the export growth for the rest derivative products are dominated with the competitiveness effect. Therefore, it needs to be implemented efforts to enhance the competitiveness of dairy derived products IndonesiaKeywords: milk, competitiveness, revealed comparative advantage (RCA), export product dynamic (EPD), constant market share analysis (CMSA)ABSTRAKPenelitian ini bertujuan (1) menganalisis daya saing komoditas susu Indonesia di pasar internasional berdasarkan keunggulan komparatif yang dimiliki, (2) menganalisis dinamika dari susu Indonesia dan menganalisis posisi daya saing komoditas tersebut di pasar internasional melalui performa produk ekspor dinamisnya, (3) menganalisis faktor-faktor dominan dalam memengaruhi pertumbuhan ekspor susu Indonesia berdasarkan analisis pangsa pasar konstan. Metode analisis yang digunakan untuk mengukur daya saing Indonesia adalah revealed comparative advantage analysis, Export product dynamic analysis (EPD), dan constant market share analysis. Hasil dari RCA menunjukkan bahwa produk turunan susu Indonesia untuk Milk not concentrated nor sweetened 1–6% fat (HS 040120), Milk and cream, concentrated or sweetened (HS 0402) and Buttermilk, curdled milk, cream, kephir, etc (HS 040390) tidak memiliki keunggulan komparatif tetapi untuk Milk and cream powder unsweetened > 1,5% fat (HS 040221), Milk and cream nes sweetened or concentrated (HS 040299) dan Cereal, flour, starch, milk preparations and products (HS19) memiliki keunggulan komparatif. Analisis EPD menemukan bahwa seluruh produk turunan susu Indonesia masuk dalam posisi rising star. Hasil analisis CMS menyimpulkan bahwa sebagain besar faktor yang signifikan memengaruhi pertumbuhan ekspor HS 040390 dan HS 0402 adalah efek pertumbuhan impor, HS 19 didominasi oleh efek komposisi komoditas dan sisanya disebabkan karena efek daya saing. Oleh karena itu, perlu dilaksanakan upaya untuk meningkatkan daya saing produk turunan susu Indonesia.Kata kunci: susu, daya saing, revealed comparative advantage (RCA), export product dynamic (EPD), constant market share analysis (CMSA)